The adventure of reason interplay between philosophy of mathematics and mathematical logic, 1900-1940 - Mancosu, Paolo (Oxford : Oxford University Press, 2010)
Paolo Mancosu presents an innovative set of studies of logic and the foundations of mathematics in the first half of the 20th century. He sheds new light on important topics such as the relationship between phenomenology and the exact sciences, the nature of truth and logical consequence, and the nature of mathematical intuition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mathematics -- Philosophy -- History -- 20th century